Integrasi Teknologi Digital dalam Pembelajaran Pendidikan Pancasila untuk Penguatan Profil Pelajar Pancasila: Integration of Digital Technology in Pancasila Education Learning to Strengthen the Profile of Pancasila Students - Riska Armianti; Yunita, Sri; Dharma, Surya (ITScience (Information Technology and Science), 2024)
Integration of digital technology in Pancasila Education learning can strengthen the development of the Pancasila Student Profile which includes six dimensions: faith and devotion to God Almighty, noble character, independence, mutual cooperation, critical thinking, and global diversity. This article aims to analyze the impact of the use of digital technology in Pancasila Education learning on strengthening student character based on the Pancasila Student profile. This study uses a qualitative method with a case study approach in elementary schools. Data were collected through observation, interviews, and analysis of learning documents. Integration of digital technology can increase student participation, facilitate collaboration, and strengthen understanding of Pancasila values. However, obstacles such as limited access to technology and teachers' digital skills need to be considered. Digital technology can play a significant role in shaping the character of Pancasila Students, but its implementation requires comprehensive support in terms of infrastructure and teacher training.